Incidence and physical properties of PSE chicken meat in a commercial processing plant - Garcia, RG; Freitas, L W de; Schwingel, A W; Farias, R M; Caldara, Fabiana Ribeiro [UNESP]; Gabriel, A M A; Graciano, J D; Komiyama, C M [UNESP]; Paz, Ibiara Correia de Lima Almeida [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2010)
It is known that PSE meat present important functional defects, such as low water holding capacity and ultimate pH, which may compromise the quality of further-processed meat products. In this study, L* (lightness), a* (redness), and b* (yellowness) values of 500 chicken breast fillets were determined using a portable colorimeter (Minolta, model CR-400) in a commercial processing plant. Fillets were considered pale when their L* was >49. Out of those samples, 30 fillets with normal color and 30 pale fillets were evaluated as to pH, drip loss, cooking loss, water holding capacity, shear force, and submitted to sensorial analysis. An incidence of 10.20% PSE meat was determined. Pale and normal fillets presented significantly different (p<0.05) pH values, L* and a* values, water holding capacity, drip loss, and cooking loss, demonstrating changes in the physical properties of PSE meat. Shear force and sensorial characteristics were not different (p>0.05) between pale and normal fillets. Despite the significant differences in meat physical properties, these were not perceived by consumers in terms of tenderness, aspect, and flavor. The observed incidence of PSE may cause losses due to its low water retention capacity.
Keywords: Meat color; meat pH; pale meat; poultry production; water retention capacity